Smart Brushing for Parallel Coordinates - Bob Laramee (IEEE Transactions on Visualization and Computer Graphics, 2019)
The Parallel Coordinates plot is a popular tool for the visualization of high-dimensional data. One of the main challenges whenusing parallel coordinates is occlusion and overplotting resulting from large data sets. Brushing is a popular approach to address thesechallenges. Since its conception, limited improvements have been made to brushing both in the form of visual design and functionalinteraction. We present a set of novel, smart brushing techniques that enhance the standard interactive brushing of a parallel coordinatesplot. We introduce two new interaction concepts: Higher-order, sketch-based brushing, and smart, data-driven brushing. Higher-orderbrushes support interactive, flexible, n-dimensional pattern searches involving an arbitrary number of dimensions. Smart, data-drivenbrushing provides interactive, real-time guidance to the user during the brushing process based on derived meta-data. In addition, weimplement a selection of novel enhancements and user options that complement the two techniques as well as enhance the explorationand analytical ability of the user. We demonstrate the utility and evaluate the results using a case study with a large, high-dimensional,real-world telecommunication data set and we report domain expert feedback from the data suppliers.